Author Correction: Colonial history and global economics distort our understanding of deep-time biodiversity (Nature Ecology & Evolution, (2021), 10.1038/s41559-021-01608-8) - Raja, Nussaïbah Begum; Dunne, Emma; Matiwane, Aviwe; Khan, Tasnuva; Nätscher, Paulina; Ghilardi, Aline Marcele; Chattopadhyay, Devapriya (Nature Ecology & Evolution, 2022)
In the version of this article initially published, the designation “Central” America was omitted in an Extended Data Fig. 2c panel heading and the caption as well as in the Extended Data Fig. 3 caption. The figure and captions have been updated to clarify “Central and South America” in each instance.
CRIS-Team Scopus Importer:2022-02-11

Colonial history and global economics distort our understanding of deep-time biodiversity - Raja Schoob, Nussaibah Begum; Dunne, Emma; Matiwane, Aviwe; Khan, Tasnuva; Nätscher, Paulina; Ghilardi, Aline Marcele; Chattopadhyay, Devapriya (Nature Ecology & Evolution, 2021)
Sampling biases in the fossil record distort estimates of past biodiversity. However, these biases not only reflect the geological and spatial aspects of the fossil record, but also the historical and current collation of fossil data. We demonstrate how the legacy of colonialism and socioeconomic factors, such as wealth, education and political stability, impact the global distribution of fossil data over the past 30 years. We find that a global power imbalance persists in palaeontology, with researchers in high- or upper-middle-income countries holding a monopoly over palaeontological knowledge production by contributing to 97% of fossil data. As a result, some countries or regions tend to be better sampled than others, ultimately leading to heterogeneous spatial sampling across the globe. This illustrates how efforts to mitigate sampling biases to obtain a truly representative view of past biodiversity are not disconnected from the aim of diversifying and decolonizing our discipline.

Endemism increases species' climate change risk in areas of global biodiversity importance - Manes, Stella; Costello, Mark J.; Beckett, Heath; Debnath, Anindita; Devenish-Nelson, Eleanor; Grey, Kerry Anne; Jenkins, Rhosanna; Khan, Tasnuva; Kießling, Wolfgang; Krause, Cristina; Maharaj, Shobha S.; Midgley, Guy F.; et al. (Biological Conservation, 2021)
Climate change affects life at global scales and across systems but is of special concern in areas that are disproportionately rich in biological diversity and uniqueness. Using a meta-analytical approach, we analysed >8000 risk projections of the projected impact of climate change on 273 areas of exceptional biodiversity, including terrestrial and marine environments. We found that climate change is projected to negatively impact all assessed areas, but endemic species are consistently more adversely impacted. Terrestrial endemics are projected to be 2.7 and 10 times more impacted than non-endemic natives and introduced species respectively, the latter being overall unaffected by climate change. We defined a high risk of extinction as a loss of >80% due to climate change alone. Of endemic species, 34% and 46% in terrestrial and marine ecosystems, and 100% and 84% of island and mountain species were projected to face high extinction risk respectively. A doubling of warming is projected to disproportionately increase extinction risks for endemic and non-endemic native species. Thus, reducing extinction risks requires both adaptation responses in biodiversity rich-spots and enhanced climate change mitigation.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Biodiversity hotspots; Extinction risk; Global-200 ecoregions; Introduced species

The overlooked realities of sampling bias - Raja, Nussaïbah Begum; Dunne, Emma; Khan, Tasnuva; Nätscher, Paulina (GSA Annual Meeting 2020, 2020)
Analyses of past global biodiversity are severely hindered by sampling biases and gaps in the fossil record. These have previously been attributed to several geological and biological factors such as rock outcrop area, taxonomic definitions, fossil abundance, among others. In many cases, inferred so-called global diversity curves only reflect regional diversity of well-sampled localities. However, global compilations of fossil occurrences, such as from the Paleobiology Database (PBDB), not only reflect the physical aspects of the fossil record, but also document the historical compilation of this data over more than two centuries. In this study, we find that socioeconomic factors such as wealth, language and security may help to explain spatial variation in the compiled data of the PBDB. Countries with high per capita gross domestic product (GDP; implying greater access to research funds), a population with high English proficiency, and greater political stability were generally found to be the countries from which higher number of collections originated and documented in the PBDB. Similarly, we found that these countries also contributed to a majority of the compiled literature from which the data was extracted. The factors identified in this study influence fossil data collection, access and availability by determining who has access to specimens and the ability to do research. As such, efforts towards achieving an understanding of the “real” past global diversity will benefit from investing in scientific education, and more research and collaborations in countries at a disadvantage, with a focus on improving local geological and paleontological knowledg